Fungsi Kognitif pada Lansia dengan Pemberian Terapi Puzzle PSTW X - Dayuningsih, Dayuningsih; Muftadi, Muftadi; Anisah, Nur; Herdalisa, Wiwie; Listyorini, Meria Woro; Sari, Novi Maya; Iksan, Ricky Riyanto; Marisi, Esther Lenny Dorlan; Rois, Amika; Zuliani, Peri (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT The increasing elderly population means that the government needs to formulate policies and programs aimed at the elderly population group so that they can play a role in development and not become a burden on society. The aim of this research is to determine cognitive function in the elderly by providing puzzle therapy at Wisma Mulia Nursing Home West Jakarta Research Quantitative with Correlation Study with cross sectional design. This research design was used because the data collection process in the study was carried out together at one time to determine the picture of cognitive function in the elderly by providing puzzle therapy. The sample in this study was 30 elderly people. Research Bivariate analysis shows statistical results in this study using a 2x2 cross table and there is no expected value < 5, so the chi square test results are 0.012 or p value < α 0.05. This means there is a significant relationship between cognitive function in the elderly and provision of PSTW X puzzle therapy. Keywords: Puzzle Therapy, Cognitive Function, Elderly.  ABSTRAK Meningkatnya populasi lanjut usia ini membuat pemerintah perlu merumuskan kebijakan dan program yang ditujukan kepada kelompok penduduk lanjut usia sehingga dapat berperan dalam pembangunan dan tidak menjadi beban bagi masyarakat. Tujuan Penelitian ini adalah mengetahui fungsi kognitif pada lansia dengan pemberian  terapi puzzle Panti Werdha Wisma Mulia Jakarta Barat Kuantitatif dengan Studi Korelasi (Correlation Study) dengan desain cross sectional. desain penelitian ini digunakan karena proses pengumpulan data pada penelitian  dilakukan secara bersama dalam satu waktu untuk mengetahui gambaran fungsi kognitif pada lansia dengan pemberian terapi puzzle Sampel pada penelitian ini adalah 30 lansia. Analisis bivariat menunjukkan hasil secara statistic pada penelitian ini menggunakan tabel silang 2x2 dan tidak ada nilai expected atau harapan < 5, maka diperoleh hasil uji chi square 0.012 atau p value <α 0.05. Ada hubungan yang signifikan antara fungsi kognitif pada lansia dengan pemberian  terapi puzzle PSTW X Kata Kunci: Terapi Puzzle, Fungsi Kognitif, Lansia